Effects of functional training on muscle strength, jumping, and functional movement screen in Wushu athletes: a systematic review - Wang, Xinzhi; Soh, Kim Geok; Deng, Nuannuan; Zhang, Dong; Cao, Shudian; Samsudin, Shamsulariffin (Elsevier, 2024)
This study aims to analyse the effects of functional training on muscle strength, jumping, and functional movement screen in wushu athletes. Methods: This study followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A systematic search of electronic databases was also conducted, including EBSCOhost, Scopus, PubMed, Web of Science, CNKI, Google Scholar, and Wanfang. The Physiotherapy Evidence Database (PEDro) scale was an effective indicator to evaluate the quality of studies included in the systematic review. Results: This systematic review included 474 participants aged 8–24 years old. The intervention period for most studies was 12 weeks. Among the included studies, 6 focused on muscle strength, 4 on jumping performance, and 11 on functional movement screen. Conclusion: These articles have been analysed, and the positive impact of functional training interventions on muscle strength, jumping, and functional movement screen of wushu athletes has been verified.